Cartels and bribes - Roberto Burguet; Elisabetta Iossa; Giancarlo Spagnolo (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
We study the relationship between collusion and corruption in a stylized model of repeated procurement where the cost of reporting corrupt bureaucrats gives rise to a free riding problem. As in Dixit (2015, 2016), cooperation among honest suppliers alleviates free-riding in reporting. However, it also facilitates collusion in bidding by increasing the value of the collusive rent. In turn, bidding collusion facilitates cooperation in reporting by increasing the value of having honest bureaucrats, generating a trade-off. When the likelihood of corruption is high and competition is weak, collusion may be a price worth paying to curb corruption.
Keywords: D44; D73; H57; L41; 330; Bribes; cartels; collusion; corruption; free-riding